Nazi scrapbooks: snapshots from Hell - Copyright Collection (Library of Congress) (2008)
"This program explores the Holocaust from a newly discovered photo album that depicts the hellish world of Auschwitz, Hitler's most notorious death camp. These rare images show life from the other side of the wire, where the banality of evil is depicted by cocktail parties, sing-a-longs and food contests of the perpetrators. This album is nothing short of a scrapbook from hell. From the hideous irony of the lighting of the Christmas tree to men drinking on a work break, this album glimpses a world where murder is reduced to the mundane. This was an Auschwitz that has gone undocumented. This show examines the story behind the story in which the album bears witness to the atrocities and a forensic examination of the photographs tells the story beyond the frame"--Copyright description.
Copyright Claimant: Creative Differences Productions, Inc. Date of Creation: 2008; Date of Publication: 2008-04-27; Registration Number / Date: PA0001636485 / 2008-05-12.
Sources used: videocassette container; Copyright catalog online; Copyright description.
Copyright Collection.
Keywords: Nonfiction television programs; Documentary television programs